Structural measures to restore Cua Tung beaches, Quang Tri province - Sao, Nguyen Tho; Anh, Tran Ngoc; Son, Nguyen Thanh; Binh, Hoang Thai (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract . This paper presents the calculations using LITPACK models, aiming to select the restoration solution for Cua Tung beach, severely eroded in recent years. The results are just the preliminary, but they are useful to direct the optimal measures to bring the beach back to its original state serving the social and economic development in Quang Tri province. Keywords: MIKE, LITPACK, erosion, cross-sections, sediment, coastline.